Evaluation of saponin-rich extracts as natural alternative emulsifiers: A comparative study with pure Quillaja Bark saponin - Schreiner, Tatiana B. (2018)
Due to synthetic surfactants' environmental impact, their replacement by natural alternatives has gained relevance, with saponins emerging as sustainable approaches. In this work, three saponin-rich extracts from different sources (Tribulus terrestris (TT), Trigonella foenum-graecum (FG), and Ruscus aculeatus (RA)) were tested as emulsifiers, and their performance compared with Quillaja Bark saponin (PS). Characterisation comprised FTIR, solubility studies, CMC assays, and emulsifying properties (emulsifying capacity (EC) and foaming capacity (FC)). For all samples, solubility assays indicated high solubility in water and low in apolar solvents (e.g., n-hexane), compatible with their O/W emulsifier character. In general, the saponin content ruled extracts' performance (PS > TT > FG > RA). EC values (without pH adjustment) were found to be 82.5, 55.0, 47.5, 36.3%, respectively. When pH changed for 7 and 9, a shift in FG and RA order was observed. The pseudo-ternary diagrams, constructed to map emulsion's composition zones, indicate the formation of single-phase systems in the region of low oil and high extract content. Except for RA extract, gel samples were formed, which are interesting technological solutions for several applications. Among the studied samples, and in alternative to PS, TT extract showed the best performance.